Inovasi Nugget Jagung dengan Memanfaatkan Hasil Panen Tanaman Jagung di Desa Balongwono oleh Mahasiswa KKNT Bela Negara UPN “Veteran” Jawa Timur - Vynka Zahira Sausan; Intan Mitayani; Safira Salma Azzahra; Hendra Maulana (Lembaga Pengembangan Kinerja Dosen, 2024)
Balongwono Village has the potential of natural resources that are very dominant, namely corn agricultural products and some of the Balongwono Village people make a living as corn farmers. The purpose of the socialization carried out by group 1 KKNT Bela Negara UPN